2021
DOI: 10.3390/jcm10204640
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota-Gut-Brain Axis as a Key to Neuropsychiatric Disorders: A Mini Review

Abstract: The central nervous system (CNS) is closely related to the gastrointestinal tract, mainly through regulating its function and homeostasis. Simultaneously, the gut flora affects the CNS and plays an essential role in the pathogenesis of neurologic and neuropsychological disorders such as Parkinson’s and Alzheimer’s disease, multiple sclerosis, amyotrophic lateral sclerosis or autism spectrum disorder. The population of gut microorganisms contains more than one billion bacteria. The most common are six phyla: Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…These bacterial species are commonly found in human small intestine, and our results are similar to previous studies of gut microbiota in AD patients. 14,28,29 Interestingly, the microbiota of the AD and AD + MD groups were more similar to that of the Con, with the exception of a reduction of Streptococcus infantis, Streptococcus sallvarius, and Bacteroides caccae in AD + MD samples (Supplementary Figure 1C). Line discriminant analysis (LEfse) revealed the differential biomarkers, which included elevated H. pylori in the AD + MD group compared to the Con group (Supplementary Figure 1E).…”
Section: Resultsmentioning
confidence: 97%
“…These bacterial species are commonly found in human small intestine, and our results are similar to previous studies of gut microbiota in AD patients. 14,28,29 Interestingly, the microbiota of the AD and AD + MD groups were more similar to that of the Con, with the exception of a reduction of Streptococcus infantis, Streptococcus sallvarius, and Bacteroides caccae in AD + MD samples (Supplementary Figure 1C). Line discriminant analysis (LEfse) revealed the differential biomarkers, which included elevated H. pylori in the AD + MD group compared to the Con group (Supplementary Figure 1E).…”
Section: Resultsmentioning
confidence: 97%
“…Faecalibaterium is one of the most abundant bacteria within the Clostridia class. Similar to patients with MS, Faecalibacterium was less abundant in patients with IBD [42] and also in patients with neurodegenerative disorders [43,44] , suggesting that Fecalibacterium may modulate the immune responses in several different diseases. Although most Clostridia bacteria were decreased in MS in our study, we found that several relatively low abundant Clostridia bacteria such as UBA1819 and Flavonifractor, were increased in MS. A role for Flavonifractor has begun to be recognized in allergy [45] ,…”
Section: Discussionmentioning
confidence: 96%
“…After the administration of dexamethasone in the DEX group, there was a significant decrease in the thick-walled phylum and instead a significant increase in the Anaphylae phylum in the intestinal flora of mice with mastitis, and another significant change in the Actinomycete phylum. Actinomyces is a filamentous Gram-positive bacterium with a higher GC content compared to another group of Gram-positive bacteria in the gut microbiota, Firmicutes ( Stopinska et al, 2021 ). One of the most striking features of Actinomycetes has been found to be their ability to produce large numbers of a wide variety of antibiotics ( Li et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%